Biosimilars in the United States: Market Dynamics and Patient Out-of-Pocket Costs - Dayer, Victoria (My University, 2026)
BackgroundThe United States biosimilars market is growing rapidly and has led to significant savings for the health care system and payers. However, market complexities, barriers to entry, and fewer biosimilars in the pipeline than expected has led to concerns about the long-term sustainability of the biosimilars market and therefore threatened savings. We characterized eight physician-administered biologics markets in terms of price declines and reference product market share to better understand the heterogeneity between these markets. We also estimated the effect of biosimilar competition on patient out-of-pocket costs for rheumatology biologics, to understand whether biosimilar competition is truly resulting in savings for patients. MethodsFor Aim 1, quarterly average sales price (ASP) data from the Centers for Medicare and Medicaid Services (CMS) Drug Pricing Files along with volume data from the standard Medicare Limited Data Set (5% sample) for Medicare and the MerativeTM MarketScan® Commercial Database for the commercial population were used as data sources, using price and volume (number of claims) for the following biologics: filgrastim, rituximab, infliximab, trastuzumab, pegfilgrastim, epoetin alfa, bevacizumab, and ranibizumab. We first characterized the markets descriptively, then used linear regression to assess the relationship between reference product market share and each biosimilar entry and to study biosimilar versus reference product price decline over time since biosimilar entry. For Aim 2, the MerativeTM MarketScan® Commercial Database was used to conduct an analysis of patient OOP costs before and after biosimilar competition using the methodology described by Callaway & Sant’Anna. We included infliximab, rituximab, and adalimumab as the drug groups of interest, as they are the rheumatology biologics with biosimilars available. The exposure was biosimilar competition and the outcome was biologic-related OOP costs. ResultsIn Medicare, reference product market share declined consistently, though to varying degrees across molecule groups. In the commercial sector, market share trends were more variable, with some reference product markets remaining stable and others declining steeply. Price trends also differed substantially between payer sectors. In Medicare, biosimilars showed an 18.6% (p<0.01) greater price decline on average than reference products, while in commercial markets the overall result was not significant. Price decline patterns varied widely between the different biologics. For patient out-of-pocket costs, we observed statistically significant savings due to biosimilar competition, with an average savings of over $1,000 in the infliximab and rituximab groups over the study period. When assessing treatment effect by duration of exposure, we observed increasing savings over time, the longer biosimilars were available. In the adalimumab group, there was an increase in patient OOP costs in the year prior to biosimilar availability, which may reflect anticipatory price increases on the part of the reference manufacturer. There was minimal savings in the adalimumab group upon biosimilar entry, and no savings when accounting for one year of anticipation. ConclusionThe first study provides evidence of the differences between biologic markets in both market share and price decline trends, and the challenge of generalizing predictions or drawing generalizable conclusions about biosimilar market behavior. The second study indicates that the availability of infliximab and rituximab biosimilars led to significant savings for patients in addition to the health care system as a whole, with more savings the longer biosimilars are on the market. Together, these studies highlight the importance of policies that incentivize development of biosimilars and support the long-term availability of biosimilars to preserve and increase savings for patients.
Thesis (Ph.D.)--University of Washington, 2025
Keywords: Biologics; Biosimilars; Commercial; Costs; Medicare; Pharmaceutical sciences; Health sciences; Economics; To Be Assigned